DAMPAK PENYAKIT MULUT DAN KUKU TERHADAP PRODUKSI, KUALITAS SUSU SAPI PERAH, DAN PENERIMAAN PETERNAK DI WILAYAH KERJA KSU TANDANGSARI: FOOT ANDA MOUTH DISEASE IMPACT ON PRODUCTION, DAIRY COW MILK QUALITY, AND INCOME OF DIARY FARMER IN KSU TANDANGSARI WORKING AREA - Ariska, Trisna; Hermawan, Hermawan; Firman, Achmad (Universitas Djuanda, 2024)
The study entitled Foot and Mouth Disease Impact on Production, Dairy Cow Milk Quality, and Income of Dairy Farmer in KSU Tandangsari Working Area has been carried out in Farmer Groups which incorporated in KSU Tandangsari for 4 weeks in January, 2024. The objective of this study was to analyze the production, milk quality, and population of dairy cows in the KSU Tandangsari working area before and during FMD and analyze the effect of FMD on farmers' income. The method of this research a survey method, involving 87 respondents from selected farmer groups namely Mekarsari, Wargi Saluyu, and Harapan Jaya with random sampling method which was analyzed by quantitative descriptive method. The result of this study showed that in KSU Tandangsari there was a decline in milk production and dairy cow population during the outbreak of FMD, further results showed that there was a higher decline in the period one year after FMD outbreak compared to the period before the FMD outbreak. The quality of milk is not affected by FMD and the quality still able to reach the SNI 3141.1 of 2011 about fresh milk quality requirements. FMD outbreak significantly affected farmers' income (P<0.05), resulting in a 35% reduction in income compared to the period before the FMD outbreak